2017
DOI: 10.1155/2017/9738640
|View full text |Cite
|
Sign up to set email alerts
|

Time- and Dose-Dependent Effects of 17 Beta-Estradiol on Short-Term, Real-Time Proliferation and Gene Expression in Porcine Granulosa Cells

Abstract: The key mechanisms responsible for achievement of full reproductive and developmental capability in mammals are the differentiation and transformation of granulosa cells (GCs) during folliculogenesis, oogenesis, and oocyte maturation. Although the role of 17 beta-estradiol (E2) in ovarian activity is widely known, its effect on proliferative capacity, gap junction connection (GJC) formation, and GCs-luteal cells transformation requires further research. Therefore, the goal of this study was to assess the real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
0
23
0
3
Order By: Relevance
“…Moreover it was defined that proper regulation of these processes is required for complete maturation of oocytes. Our previous studies have shown various aspects of changes occurring in oocytes during maturation [1][2][3] and impact of environmental changes on these processes [4][5]. Morphological and biochemical alterations associated with the ability of embryo to formation of blood vessels networks seem to play pivotal role in successful implantation, decidualization and early embryo -maternal interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it was defined that proper regulation of these processes is required for complete maturation of oocytes. Our previous studies have shown various aspects of changes occurring in oocytes during maturation [1][2][3] and impact of environmental changes on these processes [4][5]. Morphological and biochemical alterations associated with the ability of embryo to formation of blood vessels networks seem to play pivotal role in successful implantation, decidualization and early embryo -maternal interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between generative hormones level and connexin (Cx) has been well studied. Estrogens could lead to the increased expression of Cx43 in rat [32][33][34] and pig [35]. The appearance of the gap and the decrease of the molecules expression level involved in interaction between granulosa cells and oocyte may have blocked the signaling, nutrition, growth factor and steroids transmitting between granulosa cells and oocytes, which induced the apoptosis of granulosa cells and affected the maturation of oocyte and resulted in reduced ovary size (Figure 2(a,b)), as well as oocyte maturation rate ( Figure 6(a,b)).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we introduced the primary culture systems based on: (1) human ovarian granulosa cells, (2) porcine ovarian granulosa cells, (3) porcine endometrial and myometrial cells, and (4) porcine epithelial oviductal cells (OECs) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%